Comparision of dynamic and static balance in adolescents handball and soccer players - (:unkn) unknown (My University, 2014)
0

This study aims to compare the static and dynamic balance in adolescents handball and soccer players. 32 male student national athletes: soccer (N= 17), handball (N= 15) between 15-18 years of age and at least 3 training years were included to the study. Assessment of static and dynamic balance was measured with Prokin 5.0 Technobody. There were no significant differences found between handball and soccer players on static and dynamic balance tests. We think that there are similar movements used often by both group, like faking and changing direction. On the other hand, there was found significant difference between right and left leg of soccer players perimeter scores for unipedal (Forward-Backward) dynamic balance slalom tests, when were compared within each group { t (15)= -3,158, p < 0,01 }. Unipedal (F-B) dynamic balance slalom tests score of right leg was better than left leg for soccer players, but, there were no significant differences for handball players (p>0,05). All of the soccer players are dominantly using their right leg. In addition, this result might relate training methods and years, experience, muscle force asmmetry. On the other hand, handball players s dominant legs are also right, but their usually jumping legs are left.
Keywords: Tarih